2019
DOI: 10.1038/s41467-019-13135-z
|View full text |Cite
|
Sign up to set email alerts
|

A neural network for information seeking

Abstract: Humans and other animals often show a strong desire to know the uncertain rewards their future has in store, even when they cannot use this information to influence the outcome. However, it is unknown how the brain predicts opportunities to gain information and motivates this information-seeking behavior. Here we show that neurons in a network of interconnected subregions of primate anterior cingulate cortex and basal ganglia predict the moment of gaining information about uncertain rewards. Spontaneous increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
159
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(185 citation statements)
references
References 110 publications
24
159
2
Order By: Relevance
“…By contrast, recent work has shown that uncertainty reduction and information gain are indeed reflected in neural RL computations [60]. Evidence from fMRI studies suggests that corticostriatal circuits incorporate the utility of information in reward computations, such that information is conceptualized as a reward that reinforces choices [61], even when it is not valenced [59]. The prefrontal cortex also appears to track information and uncertainty [40], which can be held in working memory to influence decision making [62] ( Figure 4).…”
Section: Rewards and Expectationsmentioning
confidence: 93%
See 1 more Smart Citation
“…By contrast, recent work has shown that uncertainty reduction and information gain are indeed reflected in neural RL computations [60]. Evidence from fMRI studies suggests that corticostriatal circuits incorporate the utility of information in reward computations, such that information is conceptualized as a reward that reinforces choices [61], even when it is not valenced [59]. The prefrontal cortex also appears to track information and uncertainty [40], which can be held in working memory to influence decision making [62] ( Figure 4).…”
Section: Rewards and Expectationsmentioning
confidence: 93%
“…One such example relates to the value of information. Humans are motivated to reduce uncertainty about their environment [59]. Thus, acquisition of novel information should in itself function as reinforcement.…”
Section: Rewards and Expectationsmentioning
confidence: 99%
“…Curiosity about lottery outcomes was shown to disinhibit the ACC in humans via the increased amplitude of a "feedback-related negativity" EEG signal that is believed to be related to dopaminergic projections to the ACC [68]. ACC was also shown to be responsive to anticipation of information during an observing task in monkeys [31].…”
Section: Involvement Of Control Areas In Curiositymentioning
confidence: 99%
“…Specifically, the apparent preference for advance information could be accounted for by greater levels of attentional engagement on informative trials, leading to increased associative learning for informative cues, and thus promoting their choice even in the absence of curiosity [27]. The general argument is plausible, and differential attention may explain some of the effect; however, it appears insufficient to explain several results [18,30,31]. To give one example, lateral habenula neurons reliably signal information prediction errors for informative as well as uninformative cues, indicating that animals do not forget their reward predictions due to task disengagement even in uninformative trials [32].…”
Section: The Observing Taskmentioning
confidence: 99%
See 1 more Smart Citation